Nystagmus goggles: how to use them, what you find and what it means. Issue 6 (28th October 2020) - Halmagyi, G Michael; McGarvie, Leigh A; Strupp, Michael
Abstract : A fundamental characteristic of peripheral vestibular nystagmus, in particular horizontal nystagmus, is that it is suppressed by visual fixation. This means that a patient with a vertigo attack of peripheral vestibular origin might have no obvious spontaneous nystagmus on clinical examination. Goggles that reduce or remove visual fixation allow the cliniican to observe nystagmus in this situation. Nystagmus goggles are essential for any clinician dealing with dizzy patients. Here, we discuss why this is so and how easy it is to acquire and use them.